Studi Jumlah Penyebaran Kendaraan setelah Pengoperasian Fly Over pada Persimpangan Jl. A. H. Nasution dengan Jl. Jamin Ginting - Muhammad Abdhi Ridha (Syntax Idea)
Congestion is a common problem in transportation. Congestion can be caused by several things, one of which is the continued increase in population and the increasing number of immigrants who settle. This also happens in the city of Medan, especially at the intersection of Jalan A.H. Nasution and Jamin Ginting road. This rapid growth causes the volume of traffic at this location to increase, resulting in frequent traffic jams during rush hour. Seeing these problems, the Medan City government decided to build a flyover at the intersection location as a solution to overcome traffic jams. Which started in July 2012 and was completed in January 2015 and inaugurated on February 28 2015. However, is this construction currently able to overcome the congestion that occurs at this intersection? Therefore, this research was conducted to determine the effect of the flyover operation on the number of vehicles distributed at the intersection. Based on the results of the survey and analysis carried out at the intersection of Jl A.H Nasution and Jl Jamin Ginting, the highest traffic volume values were obtained at the intersection of Jl A.H Nasution (1812 vehicles/hour) and the flyover from the direction of Jl A.H. Nasution (4017 kend/hour) which occurred on Monday. The highest capacity value was on Monday afternoon on Jl. The highest degree of saturation value was obtained on Monday afternoon on Jl Ngumban Surbakti (0.951). So based on the indicator values obtained, it shows that the construction of flyovers as an alternative to reduce traffic jams is considered quite effective in accordance with the 1997 MJKI regulations which state that the value Maximum Degree of Saturation for urban areas is >1. This is also proven by the small number of vehicles crossing the intersection and conversely the number of vehicles crossing the flyover above it is quite large.